The Prevalence and Factors Associated with Prophylactic Antibiotic Use during Delivery: A Hospital-Based Retrospective Study in Palembang, Indonesia - Ariesti Karmila; Mohammad Zulkarnain; Abarham Martadiansyah; Putri Mirani; Nuswil Bernolian; Joseph C. Gardiner; Lixin Zhang (MDPI AG, 2021)
Prophylactic antibiotic usage during delivery is a common practice worldwide, especially in low- to middle-income countries. Guidelines have been published to reduce antibiotic overuse; however, data describing the use of prophylactic antibiotics and clinician adherence to guidelines in low- to middle-income countries remain limited. This study aimed to describe the prevalence of prophylactic antibiotic use, factors associated with its use, and clinician adherence to guidelines. A retrospective review was conducted for all deliveries from 1 January 2016 to 31 December 2018 at a tertiary level hospital in Indonesia. The prevalence of prophylactic antibiotic use during delivery was 47.1%. Maternal education level, Ob/Gyn specialist-led delivery, a history of multiple abortions, C-section, premature membrane rupture, and antepartum hemorrhage were independently associated with prophylactic antibiotic use. Clinician adherence to the guidelines was 68.9%. Adherence to guidelines was the lowest in conditions where the patient had only one indication for prophylactic antibiotics (aOR 0.36, 95% CI 0.24-0.54). The findings showed that the prevalence of prophylactic antibiotic use during delivery was moderate to high. Adherence to local guidelines was moderate. Updating the local prescribing guidelines may improve clinician adherence.